2018
DOI: 10.1002/jcp.27827
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: IRAK3 gene silencing prevents cardiac rupture and ventricular remodeling through negative regulation of the NF‐κB signaling pathway in a mouse model of acute myocardial infarction

Abstract: Cardiac rupture and ventricular remodeling are recognized as the severe complications and major risk factors of acute myocardial infarction (AMI). This study aims to evaluate the regulatory roles of interleukin‐1 receptor‐associated kinase 3 (IRAK3) and nuclear factor‐κB (NF‐κB) signaling pathway in cardiac rupture and ventricular remodeling. Microarray analysis was performed to screen AMI‐related differentially expressed genes and IRAK3 was identified. The models of AMI were established in male C57BL/6 mice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Interleukin 1 receptor associated kinase 3 (IRAK3), which encodes a member of the IL-1 receptor-associated kinase protein family, functions as a negative regulator of Toll-like receptor signaling and participates in innate host defense and in the control of adaptive immune responses (39). Evidence in a mouse model of AMI demonstrated that IRAK3 gene silencing could minimize AMI damage, indicated by a reduced infarct area and collagen content (40). A mutation in the thrombomodulin (THBD) gene is the main cause of thromboembolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 1 receptor associated kinase 3 (IRAK3), which encodes a member of the IL-1 receptor-associated kinase protein family, functions as a negative regulator of Toll-like receptor signaling and participates in innate host defense and in the control of adaptive immune responses (39). Evidence in a mouse model of AMI demonstrated that IRAK3 gene silencing could minimize AMI damage, indicated by a reduced infarct area and collagen content (40). A mutation in the thrombomodulin (THBD) gene is the main cause of thromboembolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NF‐κB still exerts impacts on oxidative stress, genotoxic stress and the self‐regulation of homeostatic functions . Activated NF‐κB signalling pathway can be observed in myocardial tissues from AMI mouse model, while impaired NF‐κB signalling pathway could impede the cardiac rupture and ventricular remodelling . However, investigations on the roles of lncRNAs and NF‐κB and their interaction in MI are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is the newest identified member of the MMP family and it has been documented that MMP-28 protein levels decrease in response to pathological conditions [ 45 ]. In contrast to MMP-2 and MMP-9 where myocardial infarction (MI) induced increase of their levels/activities [ 46 , 47 ], MMP-28 levels decreased post-MI [ 45 ]. Moreover, deletion of MMP-28 increased dysfunction of the left ventricle post-MI by reduction of inflammatory and fibrotic responses.…”
Section: Discussionmentioning
confidence: 99%